2017
DOI: 10.18632/oncotarget.18062
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphisms in the antioxidant genes CAT, GR and SOD1, erythrocyte enzyme activities, dietary and life style factors and breast cancer risk in a Danish, prospective cohort study

Abstract: Exposure to estrogens and alcohol consumption - the two only well-established risk factors for breast cancer - are capable of causing oxidative stress, which has been linked to progression of breast cancer. Here, five functional polymorphisms in the antioxidant genes SOD1, CAT and GSR were investigated in 703 breast cancer case-control pairs in the Danish, prospective “Diet, Cancer and Health” cohort together with gene-environment interactions between the polymorphisms, enzyme activities and intake of fruits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…Exposure to estrogens and alcohol consumption -the two only well-established risk factors for breast cancer -are capable of causing oxidative stress, which has been linked to progression of breast cancer. Our results showed that genetically determined variations in the antioxidant enzyme activities of SOD1, CAT and GSR were not associated with risk of breast cancer 49 . Succinic acid production from fruit and vegetable wastes hydrolyzed by on-site enzyme mixtures through solid state fermentation.…”
Section: Introductionmentioning
confidence: 55%
“…Exposure to estrogens and alcohol consumption -the two only well-established risk factors for breast cancer -are capable of causing oxidative stress, which has been linked to progression of breast cancer. Our results showed that genetically determined variations in the antioxidant enzyme activities of SOD1, CAT and GSR were not associated with risk of breast cancer 49 . Succinic acid production from fruit and vegetable wastes hydrolyzed by on-site enzyme mixtures through solid state fermentation.…”
Section: Introductionmentioning
confidence: 55%
“…Polymorphisms of SOD1 gene may affect the enzymatic activities, leading to altered antioxidant defense. Several studies have evaluated the influence of SOD1 polymorphisms in patients with cirrhosis, cardiovascular disease, and cancer; however, there have been no previous studies in patients with septic shock [11][12][13]32].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these polymorphisms can affect protein structure and function, leading to altered enzymatic responses. The decreased activity of antioxidant enzymes could lead to oxidative stress and affect the risk and prognosis of several diseases [11]. Variation in the SOD1 gene has been found to be associated with cardiovascular deaths in the general population, and the SNP rs1041740 might be associated with the development of ascites in patients with cirrhosis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant genes included SOD1 (5′-GCGGCGTTATTGGCATTG-3′, 3′-ACTAACAGACCACAGGCTATG-5′), SOD2 (5′-CACATCAACCACACCATCTTC-3′, 3′-GCTCTTCCACTGC GACTC-5′) and CAT (5′-TGAACTTCCTGGATGAGATGTC-3′, 3′-TCTTGGCGGCACAATACTG-5′), which were normalized with RP49 (5′-AGGGTATCGACAACAGAGTG-3′, 3′-CACCAGGAACTTCTTGAATC-5′), a housekeeping gene used for normalization. The expression of the target genes was calculated using the 2−ΔΔCt method [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%